ANALISIS KEMAMPUAN BERPIKIR REFLEKTIF MATEMATIS SISWA MATERI PERSAMAAN LINIER DUA VARIABEL KELAS VIII SMPN 8 SINGKAWANG - Budiarti, Ismi; Citroresmi, Nindi; Wahyuni, Rika (CV. Lafadz Jaya, 2024)
The objectives to be achieved in this study are to analyze the level of students' mathematical reflective thinking ability on the material of linear equations of two variables, to analyze what are the forms of errors in students' mathematical reflective thinking ability on the material of linear equations of two variables and to analyze what are the factors that influence errors in students' mathematical reflective thinking ability on the material of linear equations of two variables. The type of research that will be used in this research is descriptive, while for the research approach, it will use a qualitative approach. The mathematical reflective thinking ability of each category is high (0%), medium (3.33%), low (96.77%). In general, it is obtained that the level of students' reflective thinking ability is low.